Innovation and Technological Change: ITS Impact on Demand and Supply in the Market - Fitri Rachmiati Sunarya; Fuad Arrasyid Almubarok; Irfan Ali Baihaqi; Fitria Insani; Puji Rahmawati (Publikasi Indonesia, 2024)
Innovation and new technologies have the potential to change markets and create opportunities for new and innovative companies. This article aims to analyse the impact of innovation and technological change on demand and supply in the market. In this research, a case study was carried out on the consumer technology market and an analysis of the technology stock market. The author uses data from various sources such as surveys, literature reviews, and social media. The results of this study show that innovation and technological change can increase demand in certain markets, such as the mobile phone market or the computer software market, but can also shift demand in certain sectors, such as in more traditional industrial fields. In addition, innovation and technological change can also affect supply in the market due to pressure to increase efficiency through automation and better use of technology. However, innovation and technological change also create new competition and benefit consumers in terms of price and quality. In its conclusion, this study concludes that innovation and technological change are important factors in determining demand and supply in the market and must be taken into account by companies and governments when formulating their market strategies